2019
DOI: 10.1590/0037-8682-0199-2018
|View full text |Cite
|
Sign up to set email alerts
|

Rabies virus monitoring in bat populations in Rondônia state, Brazil

Abstract: Introduction: The Jirau hydroelectric power plant built in Rondônia state has environmental impacts that could be relevant to rabies outbreaks. Methods: Bat populations were monitored for rabies by fluorescent antibody testing and simplified fluorescent inhibition microtesting between 2010 and 2015. Results: All 1,183 bats tested negative for rabies. The prevalence of rabies antibodies was 17.5% in 1,049 bats. Conclusions: The rabies antibody dosage was not reactive in samples collected before the environmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
0
6
0
1
Order By: Relevance
“…(b) PCA of microsatellite data for nine loci (n = 69 individuals, 64 alleles). Shown are the first two axes of the PCA with points coloured by site and grouped using concentration ellipses could have elevated seroprevalence (Almeida et al, 2019;Ellison et al, 2014). More broadly, the high frequency of seropositive individuals here provides further evidence that many apparently healthy bats are exposed to RABV and can clear peripheral viral infection without showing disease (Ellison et al, 2014;Streicker et al, 2012;de Thoisy et al, 2016;Turmelle, Allen, et al, 2010;.…”
Section: Discussionmentioning
confidence: 67%
“…(b) PCA of microsatellite data for nine loci (n = 69 individuals, 64 alleles). Shown are the first two axes of the PCA with points coloured by site and grouped using concentration ellipses could have elevated seroprevalence (Almeida et al, 2019;Ellison et al, 2014). More broadly, the high frequency of seropositive individuals here provides further evidence that many apparently healthy bats are exposed to RABV and can clear peripheral viral infection without showing disease (Ellison et al, 2014;Streicker et al, 2012;de Thoisy et al, 2016;Turmelle, Allen, et al, 2010;.…”
Section: Discussionmentioning
confidence: 67%
“…Given ongoing rabies outbreaks in Belize, sampling bats during the epizootic could have facilitated a higher likelihood of detecting seropositive bats, as VNAs from recent viral exposures would not yet have waned to undetectable levels (Jackson et al, 2008;Plowright et al, 2019). Vampire bats in our sites also co-roost with other bat species, including Glossophaga soricina and Trachops cirrhosus (Fenton et al, 2001), which have tested positive for RABV VNA in other countries, so exposures to non-vampire bat RABV variants could have elevated seroprevalence (Ellison et al, 2014;Almeida et al, 2019). More broadly, the high frequency of seropositive individuals here provides further evidence that many apparently healthy bats are exposed to RABV and can clear peripheral viral infection without showing disease Streicker et al, 2012;Ellison et al, 2014;de Thoisy et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The article entitled "Rabies virus monitoring in bat populations in Rondônia state, Brazil" is very interesting 1 . Almeida et al 1 conducted a molecular and serological assessment for the presence of the rabies virus in bats in the area surrounding the Jirau hydroelectric power plant in Rondônia state, Brazil. They found that all 1,183 bat brains analyzed were negative for the presence of rabies virus, and antibodies were noted in 17.5% of 1,049 bats.…”
Section: Dear Editormentioning
confidence: 99%